Analysis of the performance of biathlon sports national team of Russia throughout the season 2015-2016 - Zagursky, N. S.; Romanova, Y. S.; Mikhalev, V. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2016)
The article analyzes the competitive activity of the strongest biathlon commands in the World championship 2016 and World Cup stages throughout the season 2015-2016. Distribution of medals in the World championship of 2016 on biathlon has been shown; the rating of the strongest biathlon commands in the season of 2015-2016 has been presented. The basic indicators of the competitive activity of 30 strongest men and women throughout the season 2015-2016 have been revealed the comparative analysis of racing and shooting readiness of winners of the World Cup and the Russian biathlon participants throughout the season 2015-2016 has been given.